The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ac901086k
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Method for the Quantitative Assay of Ketoconazole in Pharmaceutical Preparations

Abstract: In this study, electron paramagnetic resonance (EPR) is used, for the first time, as an analytical tool for the quantitative assay of ketoconazole (KTZ) in drug formulations. The drug was successfully characterized by the prominent signals by two radical species produced as a result of its oxidation with 400 microg/mL cerium(IV) in 0.10 mol dm(-3) sulfuric acid. The EPR signal of the reaction mixture was measured in eight capillary tubes housed in a 4 mm EPR sample tube. The radical stability was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…This lead supports the analysis of the KTZ-oxidation products in more details. It is also indicates that, unlike our earlier investigation of the chemical oxidation of KTZ-radical species [18] that suggested KTZ oxidation produced imidazole and acetamide radical species in different proportions, the current work proves that the KTZ fragmentation occurs at the acetamide-piperazine side to produce two nitroxide radical species.…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations
“…This lead supports the analysis of the KTZ-oxidation products in more details. It is also indicates that, unlike our earlier investigation of the chemical oxidation of KTZ-radical species [18] that suggested KTZ oxidation produced imidazole and acetamide radical species in different proportions, the current work proves that the KTZ fragmentation occurs at the acetamide-piperazine side to produce two nitroxide radical species.…”
Section: Resultscontrasting
confidence: 55%
“…The present cell provided a maximal sensitivity and a minimal dielectric loss along the central axis of the EPR cavity, easy handling, and mounting with no additional adjustments, as it used a small analyte volume in a disposable capillary tube. The EC-EPR studies involving KTZ indicated that the concentration range required for acetamide radical generation was ten times (10-50 ppm) less than the concentration required for the chemical oxidation method (100-400 ppm) in the presence of Cerium(IV) in sulfuric acid media [18], as it was based on radical creating rather than radical disappearance during a chemical process analysis. The use of a graphite pencil electrode (GPE) as a working electrode surface reduced uncertainty into concentration estimates via the chemical oxidation, which required a high concentration of KTZ in multiple capillary tubes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Due to the growing interest in radical detection and identification, electron paramagnetic resonance (EPR) spectroscopy is uniquely suited as a technique for monitoring free radical kinetics. We have previously reported using EPR spectroscopy as an analytical tool for free radical intermediates generated by different oxidation processes such as the irradiation of alanine [ 19 ] and the chemical and electrochemical oxidations of active ingredients in drug formulations [ 20 , 21 ]. In this work, we report the investigation of the free radical reactions of anthracene in concentrated sulfuric acid using EPR spectroscopy, which can be seen as a model system for other PAHs.…”
Section: Introductionmentioning
confidence: 99%